Perancangan Ulang UI/UX Website SMPN 3 Genteng Menggunakan Metode Design Thinking - Putri, Safira Tsani Amelya; Umam, Khoirul; Panduardi, Farizqi; Prasetyo, Junaedi Adi; Hidayat, Alfin (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
SMPN 3 Genteng faces challenges in providing information that is easy to understand and visually appealing to users. The current website has a disorganized layout, making it difficult for users to find information about school services. An evaluation using the System Usability Scale (SUS) revealed a usability score of 41.58, rated as